THE CORRELATION BETWEEN READING COMPREHENSION AND WRITING ABILITY ON DESCRIPTIVE TEXTS OF THE SECOND YEAR STUDENTS OF SMAN 2 BATAM - Yenni Rahmayani; Atni Prawati; Novitri ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The objective of this research is to find out the correlation between reading comprehension and writing ability on descriptive texts of the second year students of SMA 2 Batam. The sample of this research was class XI IPA, which consist of 30 students. The data were collected by using two kinds of test, reading comprehension test and writing test. The result of this research showed that the second year students of SMAN 2 Batam got good level with the average score of 74.06 in reading comprehension and in writing test, the students got adequate level with average score 68.43. The result of this research proved that there is a positive correlation between reading comprehension and writing ability on descriptive texts. The rxy distribution of the coefficient correlation is 0.69. It means that the correlation was in moderate level. So, Ha (alternative hypothesis) of this research is accepted and null hypothesis (Ho) is rejected. In other words, it can be concluded that this correlation cannot prove that students who are good in reading will also have the same ability in writing. This can be seen on the students’ score of reading and writing. There are some students who got good scores in reading test, but got bad scores in writing. There is a tendency where the students’ reading score was in accordance with their writing score and vice versa. Key Words: Correlation, Reading Comprehension, Writing Ability